Conductive pedot nanofiltration membrane and its preparation and cleaning method

CN118512927BActive Publication Date: 2026-10-27NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410705779.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-01-25
Filing Date
2024-05-31
Publication Date
2026-10-27
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

[0003]本专利所要解决的技术问题是:制备导电纳滤膜会存在膜分离性能下降、膜分离性能不好的问题

Benefits of technology

[0018]PEDOT作为一种高导电聚合物,由于其溶剂溶解性较差而面临挑战。然而,其前体EDOT在正己烷中表现出卓越的溶解性,并且在酸性质子的影响下进行自聚合,生成寡聚体PEDOT,因此,我们将EDOT引入有机相(含有TMC的正己烷溶液)参与界面聚合过程。哌嗪(PIP)和TMC的偶联导致在界面上发生激烈的反应,形成了紧密堆积的聚酰胺(PA)层,同时伴随着盐酸(HCl)的生成。与此同时,HCl的存在导致EDOT质子化并激活其自聚合,生成PEDOT。这种导电聚合物与PIP和TMC的界面聚合反应形成的PA网络相互交织。在去离子水中浸泡后,PA网络中未反应的酰氯基团水解为羧基团。这些羧基团可以与由π共轭噻吩环导致的正电荷PEDOT建立静电相互作用,从而在图1中所示的响应性选择性层中创建相互锁定的结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118512927B_ABST
    Figure CN118512927B_ABST
Patent Text Reader

Abstract

The application discloses a PEDOT conductive nanofiltration membrane and a preparation method and a cleaning method thereof. The conductive membrane based on poly(3,4-ethylenedioxythiophene) (PEDOT) is created by coupling interface polymerization (IP) and in-situ self-polymerization of EDOT. In the IP reaction process, the generated HCl is used to initiate the protonation of EDOT, so as to activate the self-polymerization of EDOT to form PEDOT. The interwoven structure is integrated with the polyamide network to form a stable selection layer, and the permeation rate is increased by 90%. By using the conductivity of the doped PEDOT, an electrically assisted cleaning strategy is designed, and the flux recovery is fast. By using the permeation salt solution for cleaning, it is found that the electrically assisted cleaning strategy is an eco-friendly solution, which can significantly reduce the water consumption. The application provides an innovative approach for constructing a conductive membrane, and introduces an efficient and economical electrically assisted cleaning strategy to effectively solve the membrane pollution problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanofiltration membrane technology, specifically relating to a PEDOT conductive nanofiltration membrane and its preparation and cleaning methods. Background Technology

[0002] Mitigation of membrane fouling relies on effective membrane cleaning strategies, including physical and chemical methods (Lee and Elimelech, 2007). Physical cleaning methods are effective at removing contaminants from the membrane surface, but have limited effectiveness in addressing fouling within the membrane pores. In contrast, while chemical cleaning facilitates flux recovery, it can exacerbate membrane degradation, especially in the case of thin-film composite (TFC) membranes (Gohil, JM and Suresh, AK 2017. Chlorine attack on reverseosmosis membranes: Mechanisms and mitigation strategies. J. Membr. Sci. 541, 108-126.). This highlights the urgent need for innovative and efficient cleaning strategies to minimize the risk of membrane damage. Emerging electro-assisted cleaning technologies have attracted considerable attention due to their low energy consumption and absence of corrosive agents or surfactants (Kazi, OA, Chen, W., Eatman, JG, Gao, F., Liu, Y., Wang, Y., Xia, Z. and Darling, SB 2023. Material Design Strategies for Recovery of Critical Resources from Water. Adv. Mater., 2300913.). Despite significant progress in electro-cleaning of ultrafiltration membranes (Dudchenko, AV, Rolf, J., Russell, K., Duan, W. and Jassby, D. 2014. Organic fouling inhibition on electrically conducting carbon nanotube–polyvinyl alcohol composite ultrafiltration membranes. J. Membr. Sci. 468, 1-10.), the application of this technology in nanofiltration membranes remains largely unexplored, primarily due to the complex challenges of uniformly integrating conductive materials into the dense selective layers of these membranes. Summary of the Invention

[0003] The technical problem this patent aims to solve is the issue of decreased or poor membrane separation performance during the fabrication of conductive nanofiltration membranes. This invention utilizes a synergistic coupling of interfacial polymerization and in-situ self-polymerization of EDOT to produce conductive PEDOT-doped NF membranes. This unique strategy overcomes the solubility limitation of PEDOT while simultaneously generating stable, highly conductive thin-film composite (TFC) membranes. Another objective of this invention is to develop an electro-assisted cleaning strategy involving a brine cleaning solution to rapidly alleviate membrane fouling and restore flux. This innovative combination of PEDOT-doped membranes and electro-assisted cleaning significantly improves operational efficiency and cost-effectiveness compared to traditional pure water cleaning methods.

[0004] A method for preparing a PEDOT conductive nanofiltration membrane includes the following steps:

[0005] 1) Immerse the substrate in an aqueous solution containing piperazine monomers, and then remove excess solution from the membrane surface;

[0006] 2) The membrane is immersed in an oil phase solution containing acyl chloride monomers and EDOT to carry out an interfacial polymerization reaction, forming a selective separation layer on the surface of the substrate, thus obtaining an EDOT conductive nanofiltration membrane.

[0007] The piperazine monomers are selected from one or more of piperazine, piperazine hydroxide, dimethylpiperazine, trimethylpiperazine, and tetramethylpiperazine; the acyl chloride monomers are selected from one or more of trimesoyl chloride, benzoyl chloride, propionyl chloride, acetyl chloride, valerate, and octanoyl chloride.

[0008] The substrate is selected from polyimide porous membranes.

[0009] The concentration of the aqueous solution of the piperazine monomer is 0.5-5 wt%.

[0010] The mass concentration of the acyl chloride monomer in the oil phase solution is 0.01-0.5 wt%.

[0011] The mass percentage of EDOT in the oil phase solution is 0.5% to 5%.

[0012] The immersion time in step 1) is 10-500s, and the immersion time in step 2) is 5-300s.

[0013] The PEDOT conductive nanofiltration membrane prepared by the above method.

[0014] An electro-assisted cleaning method based on a PEDOT conductive nanofiltration membrane is characterized by using a PEDOT conductive nanofiltration membrane as the cathode, a titanium plate as the anode, and applying voltage while using a 1000 ppm sodium chloride solution as the electrolyte for a certain period of time.

[0015] Apply voltage of 2-10V; clean time of 1-5 minutes.

[0016] Application of PEDOT conductive nanofiltration membrane in liquid filtration.

[0017] Beneficial effects

[0018] PEDOT, as a highly conductive polymer, faces challenges due to its poor solvent solubility. However, its precursor, EDOT, exhibits excellent solubility in n-hexane and undergoes self-polymerization under the influence of acidic protons to generate the oligomer PEDOT. Therefore, we introduced EDOT into an organic phase (a hexane solution containing TMC) to participate in the interfacial polymerization process. The coupling of piperazine (PIP) and TMC leads to a vigorous reaction at the interface, forming a closely packed polyamide (PA) layer, accompanied by the generation of hydrochloric acid (HCl). Simultaneously, the presence of HCl causes EDOT to protonate and activate its self-polymerization, generating PEDOT. This conductive polymer interweaves with the PA network formed by the interfacial polymerization reaction of PIP and TMC. After immersion in deionized water, unreacted acyl chloride groups in the PA network hydrolyze into carboxyl groups. These carboxyl groups can establish electrostatic interactions with the positively charged PEDOT resulting from the π-conjugated thiophene ring, thereby achieving... Figure 1 The responsive selective layer shown creates mutually locked structures.

[0019] In water separation processes, especially those involving complex feed matrices (such as natural water or wastewater), membrane fouling is unavoidable in actual membrane separation operations. To ensure the performance and efficiency of nanofiltration membranes, cleaning is necessary to remove contaminants. An electro-assisted cleaning strategy using a brine cleaning solution was developed based on a PEDOT conductive nanofiltration membrane to rapidly alleviate membrane fouling and restore flux. Using a PEDOT conductive nanofiltration membrane as the cathode and a titanium plate as the anode, and applying a 10V voltage with a 1000 ppm sodium chloride solution as the electrolyte, cleaning for 1–5 minutes rapidly restored the flux to 98.3%. This innovative combination of PEDOT-doped membrane and electro-assisted cleaning significantly improves operational efficiency compared to traditional pure water cleaning methods.

[0020] This invention creates a conductive film based on poly(3,4-ethylenedioxythiophene) (PEDOT) by synergistically coupling interfacial polymerization (IP) with the in-situ self-polymerization of EDOT. During the IP reaction, the generated HCl initiates the protonation of EDOT, thereby activating its self-polymerization to form PEDOT. This interwoven structure integrates with the polyamide network, forming a stable selective layer that significantly increases permeability by 90%, reaching 20.4 L / m². -2 h -1 bar -1Leveraging the conductivity introduced by PEDOT doping, an electric-assisted cleaning strategy was designed, which can rapidly restore flux to 98.3% within 5 minutes, outperforming the 30-minute pure water cleaning method. Simulations were conducted using a helical winding module and cleaning with a permeate salt solution, revealing that the electric-assisted cleaning strategy is an eco-friendly solution that significantly reduces water consumption. This provides an innovative approach to constructing conductive membranes and introduces an efficient and economical electric-assisted cleaning strategy to effectively address membrane fouling, contributing to cleaner water resources and lower energy consumption. Attached Figure Description

[0021] Figure 1 (a) Schematic diagram of the fabrication process of PEDOT-doped film; (b) Polymerization reaction of PIP and TMC, self-polymerization of EDOT, and selective layer of PEDOT doping in modified film; (c) UV-Vis absorption spectra of n-hexane solution including different components; (d) ATR-FTIR spectra of EDOT, M-0, and M-2 films; (e) Sulfur element diagram (S2p) of M-0 and M-2 films with a test area of ​​420µM×320µM; (f) S 2p peak of M-0 and M-2 films measured by XPS.

[0022] Figure 2 (ae) Schematic diagram of solution composition and sampling location (f) UV-Vis detection;

[0023] Figure 3 SEM surface and (e–h) cross-sectional images of the M-0 (a, e, i), M-1 (b, f, j), M-2 (c, g, k) and M-3 (d, h, l) membranes, and (i–l) AFM spectra.

[0024] Figure 4 (a) Static water contact angle at initial and 10 s; (b) Zeta potential curves of the membrane and schematic diagram of charge cancellation between the PEDOT and PA networks; (c) Schematic diagram of resistance test of different membranes and Nyquist plot of EIS spectrum; (d) Pure water permeability of different membranes.

[0025] Figure 5 : Normalized flux and corresponding cleaning process diagrams of NF270 membrane, M-0 membrane and M-2 membrane after fouling and (a) pure water cleaning, (b) brine cleaning, (c) electro-assisted cleaning, and (d) flux decline rate.

[0026] Figure 6 EIS characterization diagrams of NF 270, M-0 and M-2 membranes.

[0027] Figure 7(a, c) Schematic diagrams of the M-2 membrane fouling cleaning process, and (b, d) the effect of cleaning time on flux recovery, where (ab) uses an electric-assisted cleaning strategy and (cd) uses a pure water cleaning strategy. Detailed Implementation

[0028] Example 1

[0029] The polyimide (PI) substrate was prepared by a solvent-inducible phase inversion method according to the method reported in previous studies (Wang, Y., Liang, RZ, Jia, TZ, Cao, XL, Wang, Q., Cao, JR, Li, S., Shi, Q., Isaacs, L. and Sun, SP2022. Voltage-Gated membranes incorporating cucurbit[n]uril molecular containers for molecular nanofiltration. J. Am. Chem. Soc. 144(14), 6483-6492. https: / / doi.org / 10.1021 / jacs.2c01263). First, the PI was dried in a vacuum oven at 70 °C for 10 hours to remove moisture. Then, 20 wt% of the dried PI was dissolved in a mixture of 64 wt% N,N-dimethylformamide (NMP) and 16 wt% polyethylene glycol 400 (PEG 400). The solution was stirred with a magnetic stirrer for 12 hours to form a homogeneous solution. The solution was allowed to stand for 6 hours to remove residual air bubbles, and then uniformly coated onto a nonwoven fabric using a 100 μm thick doctor blade. The prepared base film was washed multiple times with deionized water (DI) to thoroughly remove the solvent, and then stored in DI for later use.

[0030] A polyimide (PI) substrate was immersed in an aqueous solution containing 2 wt% piperazine (PIP) for 2 minutes, and then excess solution was removed from the membrane surface. The membrane was then immersed in a hexane solution containing 0.1 wt% trimesoyl chloride (TMC) and varying mass fractions of EDOT for 1 minute. The resulting membrane with a diameter of 10.5 cm was labeled MX, where "X" represents the mass fraction of EDOT. Detailed manufacturing information and processes can be found in [link to documentation]. Figure 1 See Table 1. All membranes were soaked in deionized water before use.

[0031] Table 1. Detailed information on membrane preparation

[0032]

[0033] EDOT was introduced into an organic phase (a hexane solution containing TMC) to participate in the interfacial polymerization process. The coupling of piperazine (PIP) and TMC led to a vigorous reaction at the interface, forming a closely packed polyamide (PA) layer, accompanied by the generation of hydrochloric acid (HCl). Simultaneously, the presence of HCl caused protonation of EDOT and activated its self-polymerization, generating PEDOT. This conductive polymer intertwined with the PA network formed by the interfacial polymerization of PIP and TMC. Upon immersion in deionized water, unreacted acyl chloride groups in the PA network hydrolyzed into carboxyl groups. These carboxyl groups can establish electrostatic interactions with the positively charged PEDOT resulting from the π-conjugated thiophene ring, thereby... Figure 1 The responsive selective layer shown creates mutually locked structures.

[0034] To elucidate the self-polymerization process of EDOT, we conducted a simulation experiment in a beaker. Using the UV-Vis spectra of a hexane solution surrounding the interface, we investigated the polymerization process of EDOT. Figure 1 (c and Figure 2). After the IP reaction, the characteristic peak of EDOT shifted from 273 nm to 275 nm, suggesting successful self-polymerization and the formation of PEDOT. Furthermore, Figure 1 d shows a point at 1610 cm -1 The unique peak at 1150–1100 cm⁻¹, attributed to -CON-, indicates the formation of the PA layer in both M-0 and M-2 films. A comparison between M-0 and M-2 reveals peaks at 1150–1100 and 870–800 cm⁻¹. -1 The new peaks within the range, corresponding to COC and CS bonds, indicate that EDOT was successfully loaded into the M-2 film. Furthermore, the COC, CS, and CC peaks of EDOT in the M-2 spectrum (1362 cm⁻¹) show significant increases. -1 ) and C=C (1480 cm) -1 The characteristic peaks of the α-CH bond shifted due to the modified conjugated structure, suggesting a transformation from EDOT to PEDOT. Successful self-polymerization yielded a 751 cm⁻¹ peak representing the =CH plane and vertical vibrations in the EDOT spectrum. -1 887 cm -1 and 1182 cm -1 The peaks supporting this disappear in the M-2 spectrum, indicating α-α coupling. Based on the uniform distribution of the S 2p line and the characteristic peaks of S 2p on the M-2 film (…),… Figure 1 (e and 1f) confirmed uniform PEDOT doping, while the N / O ratio, which decreased with increasing EDOT concentration as measured by X-ray photoelectron spectroscopy (XPS), confirmed successful loading of PEDOT within the PA layer (Table 2).

[0035] Table 2

[0036]

[0037] In this embodiment, different concentrations of EDOT were used in the IP process. The morphology of the PEDOT-doped film was characterized by scanning electron microscopy and atomic force microscopy. Figure 3 The M-0 film exhibits a typical nodular structure, while the PEDOT-doped film shows a chain-like structure. This observation suggests that the influence of EDOT on interfacial diffusion, as well as on the entanglement between the PEDOT and PA networks, likely induces these chain-like structures.

[0038] With increasing EDOT concentration, the clarity of the chain structure also improves. This improvement can be attributed to the formation of larger PEDOT aggregates, which lengthens the diffusion path and reduces the diffusion rate of PIP and TMC at the water-oil interface. This phenomenon thus expands the existing PA network, resulting in a gradually thicker, looser, and smoother selective layer. This effect is particularly pronounced when the EDOT concentration reaches 2 wt%, resulting in a lower membrane surface roughness (Ra = 8.9 ± 0.3 nm). However, further increases in EDOT concentration lead to longer and larger PEDOT chains, making them difficult to hide within the thinner PA network. Therefore, the denser chain structure significantly increases the membrane surface roughness (Ra = 35.9 ± 1.6 nm). The simultaneous occurrence of self-polymerization and IP reactions contributes to the uniform fixation of PEDOT within the PA layer of the membrane.

[0039] Besides altering the surface morphology, PEDOT doping also affects other surface properties of the film, including hydrophilicity, charge properties, and conductivity. Due to the controllable PEDOT doping over the film structure, PEDOT-doped films exhibit enhanced hydrophilicity with increasing EDOT content. Figure 4 a). The change in water contact angle (WCA) between the initial measurement and the 10-second measurement indicates that wettability improves with increasing EDOT doping. Figure 4 a). Figure 4 The charge properties described in section b show that PEDOT doping leads to a reduction in surface charge due to the electrostatic interaction between the negative charge of the PA network and the positive charge of the PEDOT chains. The significant conductivity of PEDOT results in a low resistance of 4700 Ω for the doped M-2 film in electrochemical impedance spectroscopy (EIS) measurements, highlighting its favorable conductivity. Figure 4 c). Furthermore, due to the thinner and looser selective layer caused by PEDOT doping, the M-2 membrane exhibits the highest pure water permeability. Figure 4d). Given the unique properties of the M-2 membrane—lowest surface roughness, enhanced hydrophilicity, improved wettability, reduced surface charge, favorable electrical conductivity, and highest pure water permeability—it is considered suitable for subsequent performance testing due to its predicted high permeability, antifouling properties, and response to electrical stimulation.

[0040] Membrane selectivity was evaluated by testing various solutes, including inorganic salts, dyes, and pharmaceuticals. The salt repulsion order for all tested membranes was Na₂SO₄ > MgSO₄ > MgCl₂ > NaCl, with the M-2 membrane exhibiting lower salt repulsion than the M-0 and NF₂70 membranes. The M-2 membrane, with its largest pore size, exhibited the highest permeability across a variety of solutions. This characteristic, coupled with its significant dye repulsion and low NaCl repulsion, resulted in optimal selectivity for mixed solutions such as methyl orange and NaCl. Overall, PEDOT doping does not degrade membrane performance compared to NF₂70 and M-0 membranes; rather, it should enhance electrocleanability.

[0041] Membrane fouling and cleaning

[0042] A mixed solution of sodium alginate (500 ppm) and sodium chloride (1000 ppm) was prepared, and three cycles of membrane fouling and cleaning experiments were conducted. The operating pressure and circulation flow rate were 6 bar and 72 L / h, respectively. In each cycle, the fouling process lasted for 120 minutes.

[0043] All membranes became fouled after filtration in a mixed SA and NaCl solution for 120 min, and were then cleaned using different methods: pure water cleaning, NaCl solution cleaning, and electro-assisted cleaning, each lasting 2 min. Figure 5 The contamination cleaning process was repeated for three cycles, and the flux recovery rate (FRR) and flux decline rate (FDR) were calculated after the contamination cleaning test.

[0044] The electro-assisted cleaning process used the membrane as the cathode and a titanium plate as the anode, with a 10V voltage applied and a 1000 ppm sodium chloride solution as the electrolyte. Simultaneously, the fouled membrane was cleaned with pure water and a 1000 ppm sodium chloride solution, with all cleaning processes lasting the same duration. The fouling rate and cleaning effect were visually compared using normalized flux (J), flux recovery rate (FRR), and flux decline rate (FDR), and were calculated using equations (1), (2), and (3), respectively.

[0045]

[0046]

[0047]

[0048] Where J0 is the membrane flux after 5 minutes of fouling; J r It is the membrane flux after cleaning; J a It is the real-time membrane flux.

[0049] Different membranes exhibited different fouling phenomena. NF270 and M-2 membranes showed a lighter fouling trend, attributed to the excellent hydrophilicity of the NF270 membrane and the reduction of surface charge of the M-2 membrane. The effectiveness of the cleaning strategies, in descending order, was: electro-assisted cleaning > pure water cleaning > NaCl solution cleaning. The M-2 membrane consistently demonstrated the most favorable FRR and FDR results. Figure 5 ).

[0050] Applying a 10V voltage during the electrically assisted NaCl solution cleaning process significantly increased the free radical resistance (FRR) of the NF 270, M-0, and M-2 films from 56.2%, 56.0%, and 68.1% to 86.0%, 68.0%, and 94.7%, respectively. EIS characterization ( Figure 6 The conductivity order was M-2 > M-0 > NF270 membrane. Therefore, the M-2 membrane was the preferred choice, exhibiting the most favorable cleaning results, with an FRR of 94.7% and an FDR of 5.3%. Compared with previously reported membrane cleaning effects using pure water, the electro-assisted cleaning method proposed in this study, especially for the M-2 membrane, demonstrated excellent recovery capability, rapidly restoring the flux to 94.7% and 98.3% of its initial value within 1 and 5 minutes, respectively.

[0051] like Figure 7 As shown, a comprehensive evaluation of the economic feasibility of nanofiltration (NF) processes for water treatment using M-2 membranes and an electro-assisted cleaning strategy was conducted. A mixed solution of SA and NaCl was used as the feed solution for the NF process, where SA was repelled by the M-2 membrane and NaCl was permeated, representing the separation of organic and inorganic salts. After 120 minutes of operation, a 2-minute electro-assisted cleaning procedure was performed using the permeated sodium chloride solution as the cleaning agent for a laboratory-made membrane (Table 2). This was compared to a process where the M-2 membrane was simultaneously cleaned with pure water. The results demonstrated the advantage of the electro-assisted cleaning strategy, proving that it restored membrane flux to over 94% in a short time of 2 minutes. In contrast, the pure water cleaning strategy required 30 minutes or more to achieve a similar flux recovery rate of 94%. Figure 7 ).

[0052] The electric-assisted cleaning procedure is shown in Table 3: (membrane area: 9.6 cm²) 2 Flow rate: 72 liters / hour

[0053] Table 3

[0054]

[0055] Membrane characterization methods:

[0056] The conductivity of the membrane was analyzed by electrochemical impedance spectroscopy (EIS) in the frequency range of 1000 kHz to 0.01 Hz, with an alternating current and voltage of 50 mV RMS, using a three-electrode configuration (working electrode: 1 cm). 2 The membrane was attached to a platinum sheet; counter electrode: a 1 cm × 1 cm × 0.1 cm platinum sheet; reference electrode: Ag / AgCl; electrolyte: Ag / AgCl; electrolyte: 10 mM NaCl aqueous solution, 25 ℃). To ensure accuracy, each experiment was repeated three times, and the average value was measured.

[0057] Nanofiltration performance test:

[0058] The nanofiltration performance of the membrane was determined using a self-made cross-flow apparatus. The operating pressure and circulation flow rate were 6 bar and 72 L / h, respectively.

Claims

1. A method for preparing a PEDOT conductive nanofiltration membrane, characterized in that, Includes the following steps: 1) Immerse the substrate in an aqueous solution containing piperazine monomers, and then remove excess solution from the membrane surface; 2) The membrane is immersed in an oil phase solution containing acyl chloride monomers and EDOT to carry out an interfacial polymerization reaction, forming a selective separation layer on the surface of the substrate, thus obtaining a PEDOT conductive nanofiltration membrane.

2. The method for preparing the PEDOT conductive nanofiltration membrane according to claim 1, characterized in that, The piperazine monomers are selected from one or more of piperazine, piperazine hydroxide, dimethylpiperazine, trimethylpiperazine, and tetramethylpiperazine; the acyl chloride monomers are selected from one or more of trimesoyl chloride, benzoyl chloride, propionyl chloride, acetyl chloride, valerate, and octanoyl chloride.

3. The method for preparing the PEDOT conductive nanofiltration membrane according to claim 1, characterized in that, The substrate is selected from polyimide porous membranes.

4. The method for preparing a PEDOT conductive nanofiltration membrane according to claim 1, characterized in that, The concentration of the aqueous solution of the piperazine monomer is 0.5-5 wt%; the mass concentration of the oil solution of the acyl chloride monomer is 0.01-0.5 wt%.

5. The method for preparing a PEDOT conductive nanofiltration membrane according to claim 1, characterized in that, The mass percentage of EDOT in the oil phase solution is 0.5% to 5%.

6. The method for preparing a PEDOT conductive nanofiltration membrane according to claim 1, characterized in that, The immersion time in step 1) is 10-500s, and the immersion time in step 2) is 5-300s.

7. The PEDOT conductive nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 6.

8. An electro-assisted cleaning method based on the PEDOT conductive nanofiltration membrane of claim 7, characterized in that, A PEDOT conductive nanofiltration membrane was used as the cathode and a titanium plate as the anode. Under applied voltage, a 1000 ppm sodium chloride solution was used as the electrolyte for cleaning for a certain period of time.

9. The electrically assisted cleaning method according to claim 8, characterized in that, Apply voltage of 2-10V; clean time of 1-5 minutes.

10. The application of the PEDOT conductive nanofiltration membrane according to claim 7 in liquid filtration.

Citation Information

Patent Citations

  • PEODT conductive nanofiltration membrane as well as preparation method and cleaning method thereof

    CN118161994A